Shelter [videorecording (DVD)] - Buckley, David, 1976- (Black Bear Pictures, 2026)
"On a remote coastal island, a man living in self-imposed exile rescues a young girl from a deadly storm. This action sets off a chain of events, bringing him out of seclusion and both into harm's way. As their lives intertwine, he must navigate protecting the orphaned girl while battling enemies from his past--setting them both on a breathless odyssey for survival and a deeper journey toward redemption."--